عقد الترخيص باستغلال براءة الاختراع في إطار الأمر 03/07 (مجلة الواحات للبحوث والدراسات, 2021)
Nowadays, License Contract With The Patent Is Considered Among The Main Means Of Transmitting Technology.  It Has Become Very Important At The Level Of Economy And Law Since It Helps To Obtain Inventions, And To Exploit Them Legally And Practically. So, It Provides The Inventor With The Chance Of Publicizing His Reputation. Also, It Enables Him To Practice His Invention In Order To Win Financially. Moreover, With License Contract, The Licensee Can Get Important Inventions And Benefit From Their Practical Exploitation. Keywords-  The Patent, Licenser, Licensee, Exploitation